Transmembrane signaling and cytoplasmic signal conversion by dimeric transmembrane helix 2 and a linker domain of the DcuS sensor kinase - Stopp, Marius (J Biol Chem, 2020)
Transmembrane (TM) signaling is a key process of membrane-bound sensor kinases. The C(4)-dicarboxylate (fumarate) responsive sensor kinase DcuS of Escherichia coli is anchored by TM helices TM1 and TM2 in the membrane. Signal transmission across the membrane relies on the piston-type movement of the periplasmic part of TM2. To define the role of TM2 in TM signaling, we use oxidative Cys cross-linking to demonstrate that TM2 extends over the full distance of the membrane and forms a stable TM homodimer in both the inactive and fumarate-activated state of DcuS. An S(186)xxxGxxxG(194) motif is required for the stability and function of the TM2 homodimer. The TM2 helix further extends on the periplasmic side into the α6-helix of the sensory PASP domain and on the cytoplasmic side into the α1-helix of PAS(C). PAS(C) has to transmit the signal to the C-terminal kinase domain. A helical linker on the cytoplasmic side connecting TM2 with PAS(C) contains an LxxxLxxxL sequence. The dimeric state of the linker was relieved during fumarate activation of DcuS, indicating structural rearrangements in the linker. Thus, DcuS contains a long α-helical structure reaching from the sensory PAS(P) (α6) domain across the membrane to α1(PAS(C)). Taken together, the results suggest piston-type TM signaling by the TM2 homodimer from PASP across the full TM region, whereas the fumarate-destabilized linker dimer converts the signal on the cytoplasmic side for PAS(C) and kinase regulation.